Analysis of SARS-CoV-2 and factors predicting next spillover of its more contagious variant. - Syed Abdul Aziz; Shad, Kaneez Fatima (International Journal of Endorsing Health Science Research, 2021)
Background: At the beginning of 2020, the world has started experiencing the epidemic of a novel coronavirus; by the mid of March 2020, it has been declared a pandemic. The disease has been named COVID-19, and the virus is labelled as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) based on the type of infection it is causing. Coronaviruses are not new to us, and there are 15 different coronaviruses known to us. In the last 20 years, this is the fourth coronavirus pandemic, and SARS-CoV-2 seems to be the deadliest among all, with the ability to continue producing more contagious variants. Methodology: In this review, we used EMBASE, MEDLINE and PubMed database search engines (retrieval systems) for the words SARS-CoV-2, its origin, transmission, tropism, zoonotic, vaccines, and the factors that contribute to its contagious and virulent nature. Results: Accumulating evidence indicated that the pandemic might have a massive impact on both physical and mental health, particularly on those predisposed to COVID-19. Approved vaccines are in use around the globe, they may show different effects in future. We observe signs of constant mutation of SARS-CoV-2, recently SARS-CoV-2 variants such as delta and C.1.2. Conclusion: In this review, we endeavour to reveal the factors which can impede the ability of this highly lethal virus to reproduce into more contagious variants.